Age, socioeconomic status, and weight status as determinants of dietary patterns among German youth: findings from the LIFE child study - Hähnel, Emmelie; Sobek, Carolin; Ober, Peggy; Kiess, Wieland; Vogel, Mandy (Frontiers in Nutrition, 2025)
BackgroundMalnutrition and its consequences, such as obesity, are growing problems, especially in disadvantaged subpopulations. In order to pinpoint possible contributors to children’s nutritional habits, we examined potential determinants as age, sex, socioeconomic status, and weight status of different dietary patterns (dp) in a large German research project.MethodsThe data was collected within a population-based longitudinal cohort study. We used the Food Frequency Questionnaire (FFQ) to assess food intake in 484 children and adolescents aged 5–18 years across 1,068 visits. Cluster analysis was used to identify food groups. Study participants who consumed food groups with a similar frequency were grouped together as dietary patterns. We applied logistic and linear regression to test for whether group membership in different food groups and dietary patterns was associated with age, sex, socioeconomic status (SES), or body mass index (BMI).ResultsOverall, food consumption frequency decreased with age, including healthy foods like fruits (β = −0.39, p < 0.001) and vegetables (β = −0.17, p = 0.020). Boys consumed more meat and carbohydrates, milk/egg products, and junk food than girls did, but dietary patterns showed no significant sex differences. There was a trend toward a healthier diet with increasing SES (OR = 1.33, p < 0.001). Children with overweight or obesity were less likely to follow an infrequent diet (OROW = 0.56, p = 0.075; OROB = 0.41, p < 0.001) and were not significantly underrepresented in the healthiest pattern but were more likely to follow a neutral diet (OROW = 4.14, p = 0.042; OROB = 1.47, p = 0.504).ConclusionOur study identified age and SES as key factors in children’s and adolescents’ nutrition, highlighting their importance for improvement measures. The findings on weight and diet suggest both the complexity of obesity aetiology and potential reporting bias in certain weight groups.